Successful artificial insemination in the Asian elephant (Elephas maximus) using chilled and frozen-thawed semen - Nikorn Thongtip (2018)
Background: Artificial insemination (AI) using frozen-thawed semen is well established and routinely used for breeding in various mammalian species. However, there is no report of the birth of elephant calves following AI with frozen-thawed semen. The objective of the present study was to investigate the fertilizing ability of chilled and frozen-thawed semen in the Asian elephant following artificial insemination (AI). Methods: Semen samples were collected by from 8 bulls (age range, 12-to 42-years) by manual stimulation. Semen with high quality were either cooled to 4°C or frozen in liquid nitrogen (-196°C) before being used for AI. Blood samples collected from ten elephant females (age range, 12-to 52-years) were assessed for estrus cycle and elephants with normal cycling were used for AI. Artificial insemination series were conducted during 2003 to 2008; 55 and 2 AI trials were conducted using frozen-thawed and chilled semen, respectively. Pregnancy was detected using transrectal ultrasonography and serum progestagen measurement. Results: One female (Khod) inseminated with chilled semen became pregnant and gave birth in 2007. The gestation length was 663 days and the sex of the elephant calf was male. One female (Sao) inseminated with frozen-thawed semen showed signs of pregnancy by increasing progestagen levels and a fetus was observed for 5 months by transrectal ultrasonography. Conclusion: This is the first report showing pregnancy following AI with frozen-thawed semen in the Asian elephant. Successful AI in the Asian elephant using either chilled or frozen-thawed semen is a stepping stone towards applying this technology for genetic improvement of the elephant population. © 2009 Thongtip et al; licensee BioMed Central Ltd.